API Sebagai Inti Produk Digital dan Risiko Operasional di Lingkungan Perusahaan Modern - Reza Irsyadul Anam (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
APIs (Application Programming Interfaces) have become a key component in the development of modern digital products and the transformation of cloud-based services. Its ability to provide structured access to data and enable cross-platform integration makes APIs at the core of the enterprise's digital architecture. However, the high level of API openness poses increasingly complex security challenges, including potential data exploitation, injection attacks, credential misuse, and exploitation of business logic loopholes. This article examines the strategic role of APIs in the digital ecosystem, analyzes the operational risks that arise from API exposure, and evaluates the effectiveness of basic defense mechanisms such as API Gateways and Web Application Firewalls (WAFs). The findings of the study show that while both solutions play an important role in controlling access, filtering, and mitigating attacks at the surface layer, they have not been able to provide comprehensive protection against modern API threats that are dynamic, distributed, and often exploit weaknesses at the application and business logic levels. Therefore, a more holistic, layered, and sustainable API security approach is needed, including anomalous behavior detection, API abuse protection, and real-time monitoring to maintain the integrity and reliability of digital services.